Turtle Conservation and Education Center (TCEC) as a Corporate Social Responsibility Program in Serangan Village: The Attempt on Turtles Preserving - Utami, Dhita Hardiyanti; Tri Prasetyo Aji (Prospect Publishing, 2023)
One of PT Pertamina Patra Niaga Fuel Terminal Sanggaran Corporate Social Responsibility (CSR) activities, community-based turtle conservation is a response to phenomena that occur in its operational Ring I area. It is also sometimes referred to as the Turtle Conservation and Education Center. A community-based conservation initiative was established on Serangan Island in response to the illegal and endangering use of sea turtles. The goal of this study is to learn how the TCEC program is being implemented on Serangan Island in an effort to protect sea turtles. The qualitative data-gathering procedures used in this research method include documentation, literature reviews, and interviews. The research results showed that TCEC is believed to be capable of preserving the turtle population on Serangan Island through efforts to save turtles and relocate nests, perform surgical procedures on turtles, rehabilitate turtles, release hatchlings, and educate and socialize turtles for visitors. The conservation program at TCEC has both direct and indirect effects on society, the economy, and the environment. In addition to advancing inclusive and sustainable economic growth, productive and comprehensive job opportunities, and decent work for the residents of Serangan Traditional Village, the Turtle Conservation and Education Center (TCEC) additionally contributes to goal 15 of the Land Ecosystem by preserving three species of endangered turtles and enhancing their numbers.